Life time evaluation of PDMS stamps for UV-enhanced substrate conformal imprint lithography - Schmitt, H.; Duempelmann, P.; Fader, Robert; Rommel, Mathias; Bauer, A. J.; Frey, Lothar; Brehm, Markus; Kraft, Andreas (Microelectronic Engineering, 2012)
UV-enhanced substrate conformal imprint lithography (UV-SCIL) is a large area nano patterning technique which has the potential to find its way into industrial application. A promising application for UV-SCIL exists in the field of high brightness LEDs. Here, a surface patterning can increase the external quantum efficiency and therefore the light output of LEDs significantly. But, before UV-SCIL can be introduced as patterning technique into industrial application, process relevant parameters like the interaction between the PDMS stamp and the UV-curing material as well as the overall life time of PDMS stamps have to be evaluated. Within this work, stamps from different PDMS material compositions with a diameter of 150 mm were fabricated. These stamps were used to perform UV-SCIL with the epoxy based resist Katiobond OM VE 110707 from DELO Industrial Adhesives and it was found that the final resist layer thickness strongly depends on the PDMS material composition, the number of imprints, and the time between two subsequent imprints. This can be explained by diffusion of one or several components of the UV-curing material into the stamps, which influences the life time of the PDMS stamps. With the actual optimum PDMS material composition, 500 UV-SCIL imprints could be successfully performed without any visible degradation. © 2012 Elsevier B.V. All rights reserved.
Keywords: Life time; PDMS stamp; SCIL; Substrate conformal imprint lithography; UV-SCIL